Path Analysis Of Mediator Role For Code & Fields Of Professional Conduct In The Relationship Between Engineer Professional Performance And Consulting Engineering Services At Ministry Of Infrastructure And Urban Development In The Northern State (Journal of Namibian Studies : History Politics Culture, 2023)
This study aimed to investigate the path analysis of mediator role for rules & fields of professional behavior in the relationship between engineer professional performance and consulting engineering services at t of Infrastructure and Urban Development in The Northern State. It focuses on weakness level of adherence to rules & fields of professional behavior at the Ministry. The descriptive approach was used and a questionnaire was designed for data collection. The results reflected a partial mediator role of the rules & fields of professional behavior in the relationship between engineer professional performance and consulting engineering services with an indirect (mediated) effect of (0.46). The study emphasized that there is a need to increase the awareness of managers and engineers with regard to the importance of developing engineer professional performance to reflex on adherence to rules and fields of professional behavior & improving consulting engineering services.